1993
DOI: 10.1111/j.1398-9995.1993.tb00703.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum total IgE levels in a representative sample of a Greek population

Abstract: The distribution of IgE in a large randomly stratified Greek population sample was determined in 1187 subjects (793 men and 394 women) aged between 20 and 60 years. Skin prick testing was performed and serum total IgE expressed in iu/ml was measured by Phadebas PRIST: the data are presented as the geometric mean. Subjects were classified as atopic (257 men, 118 women) and nonatopic (536 men, 276 women) according to the results of skin testing with various aeroallergens. At any age, atopic males (120.5 vs 38 iu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 22 publications
5
12
1
Order By: Relevance
“…In line with our study findings, other studies have described higher values of total serum IgE for male children [27] and adults [6,28] as compared to females. Kulig et al [1] found significantly higher values in boys, also in a group of nonatopic children.…”
Section: Discussionsupporting
confidence: 83%
“…In line with our study findings, other studies have described higher values of total serum IgE for male children [27] and adults [6,28] as compared to females. Kulig et al [1] found significantly higher values in boys, also in a group of nonatopic children.…”
Section: Discussionsupporting
confidence: 83%
“…With regard to the lack of an age effect, although it is well known that IgE-t values increase from infancy to adolescence [19, 20], the trend in adulthood is controversial [3, 14, 21]. The lack of correlation of IgE-t with age in our study may be partly due to the limited age range that we studied (25–50 years).…”
Section: Discussioncontrasting
confidence: 53%
“…There is ample evidence that this value may vary according to the place of birth and background exposure [3,7,8,9,10]. Thus, if the diagnosis of allergy is based on IgE-t, it is imperative that the cutoff value is derived from the most recent and geographically defined normalized reference values for that locality.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations